Local pamidronate influences fracture healing in a rodent femur fracture model: an experimental study. Issue 1 (December 2016) - Menzdorf, Leif; Weuster, Matthias; Klüter, Tim; Brüggemann, Stefan; Behrendt, Peter; Fitchen-Oestern, Stefanie; Varoga, Deike; Seekamp, Andreas; Purcz, Nicolai; Glueer, Claus; Pufe, Thomas; Lippross, Sebastian
Abstract Background Bisphosphonates are a main component in the therapy of osteoporosis and other bone resorptive diseases. Previous studies have shown a positive effect of systemically applied bisphosphonates on fracture healing. Nevertheless high doses are related to side effects like osteonecrosis of the jaw, nephrotoxis and gastrointestinal symptoms. In this study we investigated the effect of locally applied pamidronate on fracture healing. Methods In a rodent model a simple femur fracture was set in female Wistar rats. We performed intramedullary fixation of the fracture and placed a collagen matrix around the fracture area. One group was treated with pamidronate, the other group with placebo via the matrix. To investigate the volume and quality of the callus we used micro-CT (μCT) and histology after 14 and 28 days. Results Our results show a positive influence of local applied pamidronate on callus volume. After 14 days an insignificant increase of callus volume in the treated animals was seen. 28 days after trauma the increase of callus volume in the treatment group was significantly higher in comparison to the control group. Osteonecrosis was not seen. Conclusions Locally applied bisphosphonates increase the callus volume in fracture healing.